A COMPARATIVE STUDY OF DIFFERENT ADDITIVE ON THE INDEX PROPERTIES OF EXPANSIVE SOILS - Agus Setyo Muntohar, Zainal Abidin (Jurnal Semesta Teknika UMY, 2001)
Expansive soils pose a detrimental for any construction that rest upon this soil. This paper presents a comparative study of different additives on the index properties of expansive soils. Three additives are used. One is lime, and two others are waste materials, calcium carbide, and rice husk ash. A laboratory study consisted of the following tests on samples treated with stabilizer: Atterberg Limits, Particle Size, and Specific Gravity. It was found that the addition of 4 % additive be able minimize plasticity index and reduce clay particle of tested samples. The results confirmed that, however, lime is more effective as stabilizer, then calcium carbide, and RHA the latest.